Opportunities to the urban air quality of characterization by the cost-effective electrochemical sensors - Antalné Bökfi, Katalin; Klucsik, Krisztián Pál; Varga, Tamás; Domokos, Endre (International Journal of Engineering and Management Sciences, 2019)
The quality of urban is more and more affected by the accelerating urbanization. The efficiency of improving air quality can be increased by providing local information on each pollutant source. The aim of our activity is providing real-time high-spatial reasultion data about air quality of the Hungarian capital city, Budapest. In this paper, results of testing and calibration of different low-cost electrochemical sensors and localization of them are represented. The first selected sensor is suitable for detecting carbon dioxide (CO2), alcohols, benzene (C6H6), nitrogen oxides (NOx) and ammonia (NH3). The RingAir initiative also aims to involve the urban population in active environmental monitoring activities, therefore in the future we are planning to implement a more detailed and continuously updated monitoring system with the participation of a Budapest bicycle courier service and some of the city’s population.